Textual amulets and writing traditions in the ancient world - Kotansky, Roy D. (Guide to the study of ancient magic, 2019)
This chapter surveys the use and construction of amulets – both “lettered” and “semi-lettered” -- in the Mesopotamian, Egyptian, Punic-Phoenician, Jewish, and Greek traditions. Each culture contributed a different and distinct history, tradition, notion of writing, and characteristic material to the development of Mediterranean amulets. The rise of amulets in the Roman period follows the development of collections of formularies as well as the popularity of gems, papyri and metal lamellae as amuletic mediums. In the end, it is argued, it is the Egyptian tradition that exerts the most powerful influence on amulets, especially the Greek lamellae.